Preparation method of two-property proton exchange membrane with net structure

By introducing side chain crosslinking structures into sulfonated aromatic polymers, the problem of insufficient stability of proton exchange membrane under high sulfonation degree is solved, high mechanical properties and ion selectivity are achieved, vanadium ion permeability is reduced, and vanadium ion permeability is improved. Battery performance and simplify the preparation process.

CN119119541AInactive Publication Date: 2024-12-13XUZHOU UNIV OF TECH

Patent Information

Application Number
CN202410092156.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-01-23
Publication Date
2024-12-13
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing sulfonated aromatic polymeric substance insufficiency has insufficient stability under high sulfonation degree, resulting in reduced transmembrane migration and mechanical properties of vanadium ions, and high cost.

Method used

Using side chain crosslinking structure, the side chain crosslinking structure of basic groups is introduced to limit the main chain space, reduce the vanadium ion transmittance, and enhance the selective transmission of ions in the membrane through acid-base interaction to build a network Structural amphoteric proton exchange membrane.

Benefits of technology

The mechanical properties and ion selectivity of the film under high sulfonation degree are achieved, the permeability of vanadium ion is reduced, the dimensional stability and battery performance of the film are improved, and the preparation method is simple and cost-effective.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119119541A_ABST
    Figure CN119119541A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a two-property proton exchange membrane with a reticular structure, which comprises the following steps: by taking a sulfonated aromatic polymer as a base material, preparing an amphoteric functionalized proton exchange membrane CS-S with the reticular structure through a cross-linking reaction of a cross-linking agent containing a multi-amino group and the sulfonated aromatic polymer; the amphoteric membranes with different crosslinking structures and crosslinking degrees are prepared by adjusting the variety and dosage of the crosslinking agent; according to the amphoteric membrane, multiple cross-linked side chains are used as base points, linear sulfonated aromatic polymer molecular chains are connected into a net-shaped structure, and the mechanical performance and the chemical stability of the proton exchange membrane are enhanced; an imino basic group on a cross-linked side chain constructs a selective proton transmission channel along the cross-linked side chain through a Donna effect and acid-base interaction between the imino basic group and a sulfonated aromatic polymer chain segment, so that the durability and the ion selective transmission performance of the CS-S two-property proton exchange membrane are improved; the process is simple to operate, low in cost and good in battery performance, is a green and energy-saving production process and is wide in application range.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of proton exchange membranes for all-vanadium liquid flow batteries, and in particular to a method for preparing a two-component proton exchange membrane with a mesh structure. Background Art

[0002] As a large-scale renewable electrochemical energy storage system, vanadium redox flow battery (VRFB) has been widely explored in recent years due to its advantages such as long cycle life, high power and low cost, and has been applied as an alternative energy storage technology for wind and solar energy systems. The VRFB system realizes the conversion between chemical energy and electrical energy through the redox reaction of vanadium ions with different valence states during the charging and discharging process, and then the protons are transferred across the membrane in the electrolyte. As one of the key components of VRFB, the proton exchange membrane (PEM) can block the cross-contamination of the positive and negative electrolytes while providing the necessary proton transmission channels. The cost and performance of PEM directly affect the battery cost, efficiency and service life. The Nafion membrane, which is currently the most widely used commercial membrane, is expensive ($600 / m 2 ), the production cost of VRFB increases accordingly. Sulfonated aromatic polymers have become a hot topic of research due to their low cost and easy availability.

[0003] For sulfonated aromatic polymer membranes, their properties depend largely on the degree of sulfonation DS. In order to obtain sulfonated aromatic polymer PEMs with excellent proton conductivity, a higher DS is required, which will lead to excessive water absorption and swelling behavior of the membrane, followed by severe transmembrane migration of vanadium ions. In addition, the increase of sulfonic acid groups will form larger hydrophilic ion domains in the membrane, which will cause the membrane to lose dimensional stability in the absence of connected hydrophobic domains to maintain structural stability, thereby reducing mechanical properties. Therefore, regulating the chemical structure of the polymer membrane, adjusting the distribution of proton transport functional groups in the membrane, and taking into account both proton conductivity and swelling degree to improve proton transfer efficiency are effective means to improve the comprehensive performance of sulfonated aromatic polymer membranes.

[0004] In the patent CN101510615B "a semi-interpenetrating network composite proton exchange membrane based on cross-linkable polyimide and its preparation method", the polyimide is first functionalized, then blended with perfluorosulfonic acid resin, and then a cross-linking agent is used to perform a cross-linking reaction to obtain a semi-interpenetrating network. This process is complex, and the cross-linking process is easily affected by the perfluorosulfonic acid resin, resulting in a complex product structure. The network structure analysis of polyimide is not systematic, and the resulting composite proton exchange membrane is expensive. Summary of the invention

[0005] Technical issues solved:

[0006] The purpose of the present invention is to overcome the problems existing in the prior art such as the insufficient stability of sulfonated aromatic polymer proton exchange membranes at high degrees of sulfonation. The present application provides a method for preparing a two-component proton exchange membrane having a network structure. The method has the characteristics of simple operation, low cost, controllable cross-linking degree, and green and pollution-free. The prepared proton exchange membrane material has high proton conductivity, mechanical properties and battery performance.

[0007] Technical solution:

[0008] To achieve the above objectives, this application is implemented through the following technical solutions:

[0009] A method for preparing a two-component proton exchange membrane having a network structure comprises the following steps:

[0010] Step A, preparation of an amphoteric polymer with a multi-crosslinked structure: sulfonated aromatic polymer: organic solvent: initiator A: crosslinker B are mixed in a mass ratio of 20 parts: 200 parts: 2 parts: 1-4 parts, the sulfonated aromatic polymer is added into a three-necked beaker, and the organic solvent is added and then stirred and dissolved; in a nitrogen environment, initiator A is added into the solution and reacted at 60° C. for 3 hours; then crosslinker B is added and the reaction is continued at 60° C. for 3 hours; after the reaction is completed, the obtained mixed solution is dialyzed with deionized water overnight, and then washed with deionized water for 3 times to wash away the unreacted monomers therein, the solid product is collected, and finally dried at 80° C. for 24 hours to obtain an amphoteric polymer with a multi-crosslinked structure;

[0011] Step B, preparation of amphoteric proton exchange membrane: the mass ratio of amphoteric polymer: organic solvent = 1 part: 8 parts, the dried amphoteric polymer obtained in step A is dissolved in the organic solution, mechanically stirred, ultrasonicated, and vacuum degassed to obtain a casting solution, which is poured into a stainless steel mold to form a membrane, and then transferred to 80°C for vacuum drying to constant weight; after vacuum drying, the obtained membrane is immersed in 2 mol / L sulfuric acid for 24 hours to completely protonate it, and then the membrane is stored in deionized water before use.

[0012] Preferably, the sulfonation degree of the sulfonated aromatic polymer in step A is above 75%.

[0013] Preferably, the sulfonated aromatic polymer is one or more of sulfonated polyetheretherketone, sulfonated polyaryletherketone, sulfonated polyarylethersulfone and sulfonated polysulfone.

[0014] Preferably, the initiator A in step A is a substance that can activate the sulfonic acid group, and the intermediate product thereof can continue to react further with the cross-linking agent B containing an amino functional group.

[0015] Preferably, the initiator A is one or more of N,N'-dicyclohexylcarbodiimide, 1-ethyl-(3-dimethylaminopropyl)carbodiimide, and N,N'-carbonyldiimidazole.

[0016] Preferably, the crosslinking agent B in step A is a substance containing polyamino groups.

[0017] Preferably, the crosslinking agent B is one or more of 2,4,6-triamino-1,3,5-triazine, tris(2-aminoethyl)amine, 2,4,6-tris(4-aminophenoxy)-1,3,5-triazine, 2,4,6-tris(4-aminophenyl)-1,3,5-triazine, tris(4-aminophenyl)amine, and triaminoguanidine hydrochloride.

[0018] Preferably, the organic solvent is an organic small molecule solvent that can dissolve the sulfonated aromatic polymer, the initiator A and the crosslinking agent B and will not react with them.

[0019] Preferably, the organic solvent is one or more of dimethyl sulfoxide, N,N'-dimethylformamide, and N,N'-dimethylacetamide.

[0020] The technical principle of the present invention is: in view of the poor stability of sulfonated aromatic polymer proton exchange membrane at high sulfonation degree, it is proposed to restrict the main chain within a certain space by using a side chain cross-linking structure to avoid excessive water absorption and swelling. In view of the high vanadium ion permeability of sulfonated aromatic polymer proton exchange membrane at high sulfonation degree, a side chain cross-linking structure with a basic group is introduced to reduce the permeation of vanadium ions by utilizing the Donnan repulsion effect of the basic group on vanadium ions and the acid-base interaction between the main and side chains. At the same time, the presence of the cross-linking structure reduces the probability of the presence of large-sized hydrophilic ion domains in the membrane, which can effectively improve the selective ion transmission in the membrane.

[0021] Beneficial effects:

[0022] The present application provides a method for preparing a two-component proton exchange membrane having a mesh structure, which has the following beneficial effects:

[0023] 1. Activate the sulfonic acid groups on the main chain of the sulfonated aromatic polymer with a high degree of sulfonation, and use them as reactive sites to introduce cross-linked side chains to construct a network structure;

[0024] 2. The side chain contains basic functional groups, which utilize the main-side chain interaction to coordinately regulate the formation of continuous hydrophilic channels and interface interactions to promote the selective transport of ions in the membrane;

[0025] 3. It can make the cross-linked amphoteric membrane have strong mechanical properties and dimensional stability, as well as high ion selectivity and low vanadium ion permeability;

[0026] 4. The preparation method is simple, energy-saving, and the cross-linking degree is controllable. It is a green and energy-saving production process with a wide range of applications;

[0027] 5. The tensile strength of the prepared proton exchange membrane is 1 times higher than that of the original sulfonated aromatic polymer membrane; compared with the commercial Nafion series membrane, the vanadium ion permeability is reduced by about 6 to 9 times, and the ion selectivity is increased by about 3 to 7 times. Description of the drawings:

[0028] Figure 1 This is a schematic diagram of the two-proton exchange membrane network structure of this application;

[0029] Figure 2 This is a stress-strain curve diagram of the two-way proton exchange membrane with a network structure prepared in Examples 1-4 of the present application. DETAILED DESCRIPTION

[0030] The preferred embodiments of the present invention are described below. It should be understood that the preferred embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0031] Embodiment 1:

[0032] A method for preparing a two-component proton exchange membrane having a network structure comprises the following steps:

[0033] Step A, preparation of an amphoteric polymer with a multi-crosslinked structure: sulfonated polyetheretherketone (SPEEK, 2 g, DS = 80%) was added to a three-necked beaker, and dimethyl sulfoxide (DMSO, 20 g) was added and then stirred and dissolved; under a nitrogen environment, N, N'-carbonyldiimidazole (0.2 g) was added to the solution and reacted at 60°C for 3 hours; then 2,4,6-triamino-1,3,5-triazine (0.1 g) was added and the reaction continued at 60°C for 3 hours; after the reaction was completed, the obtained mixed solution was dialyzed with deionized water overnight, and then washed with deionized water 3 times to wash away the unreacted monomers therein, the solid product was collected, and finally dried to obtain an amphoteric polymer with a multi-crosslinked structure (CS-S-1);

[0034] Step B, preparation of amphoteric proton exchange membrane: the amphoteric polymer (1 g) obtained in step A is dried and dissolved in dimethyl sulfoxide (DMSO) (8 g), and a casting solution is obtained after mechanical stirring, ultrasound, and vacuum degassing, which is poured into a stainless steel mold to form a membrane, and then transferred to 80°C for vacuum drying to constant weight; the obtained membrane is immersed in 2 mol / L sulfuric acid for 24 hours to completely protonate it, and then the membrane is stored in deionized water before use.

[0035] The stress-strain curve of the CS-S-1 proton exchange membrane prepared in this example is as follows: Figure 2 As shown in the figure, it can be seen that compared with the original SPEEK, the network structure constructed in the amphoteric polymer membrane by side chain crosslinking significantly enhances its mechanical properties. The vanadium ion permeability and ion selectivity data of the CS-S-1 membrane prepared in this example are shown in Table 1.

[0036] Embodiment 2:

[0037] A method for preparing a two-component proton exchange membrane having a network structure comprises the following steps:

[0038] Step A, preparation of an amphoteric polymer with a multi-crosslinked structure: add sulfonated polyetheretherketone (SPEEK, 2 g, DS = 80%) into a three-necked beaker, add dimethyl sulfoxide (DMSO, 20 g) and stir thoroughly to dissolve; under a nitrogen environment, add N,N'-carbonyldiimidazole (0.2 g) to the solution and react at 60°C for 3 hours; then add 2,4,6-triamino-1,3,5-triazine (0.15 g) and continue to react at 60°C for 3 hours; after the reaction is completed, dialyze the obtained mixed solution with deionized water overnight, then wash it with deionized water 3 times to wash away the unreacted monomers, collect the solid product, and finally dry it to obtain an amphoteric polymer with a multi-crosslinked structure;

[0039] Step B, preparation of amphoteric proton exchange membrane: the amphoteric polymer (1 g) obtained in step A is dried and dissolved in dimethyl sulfoxide (DMSO) (8 g), and a casting solution is obtained after mechanical stirring, ultrasound, and vacuum degassing, which is poured into a stainless steel mold to form a membrane, and then transferred to 80°C for vacuum drying to constant weight; the obtained membrane is immersed in 2 mol / L sulfuric acid for 24 hours to completely protonate it, and then the membrane is stored in deionized water before use.

[0040] The stress-strain curve of the CS-S-2 proton exchange membrane prepared in this example is as follows: Figure 2 The vanadium ion permeability and ion selectivity data are shown in Table 1.

[0041] Embodiment 3:

[0042] A method for preparing a two-component proton exchange membrane having a network structure comprises the following steps:

[0043] Step A, preparation of an amphoteric polymer with a multi-crosslinked structure: sulfonated polyetheretherketone (SPEEK, 2 g, DS = 80%) was added to a three-necked beaker, and dimethyl sulfoxide (DMSO, 20 g) was added and then stirred to dissolve; under a nitrogen environment, N, N'-carbonyldiimidazole (0.2 g) was added to the solution and reacted at 60°C for 3 hours; then 2,4,6-triamino-1,3,5-triazine (0.2 g) was added and the reaction continued at 60°C for 3 hours; after the reaction was completed, the obtained mixed solution was dialyzed with deionized water overnight, and then washed with deionized water 3 times to wash away the unreacted monomers therein, the solid product was collected, and finally dried to obtain an amphoteric polymer with a multi-crosslinked structure (CS-S-3);

[0044] Step B, preparation of amphoteric proton exchange membrane: the amphoteric polymer (1 g) obtained in step A is dried and dissolved in dimethyl sulfoxide (DMSO) (8 g), and a casting solution is obtained after mechanical stirring, ultrasound, and vacuum degassing, which is poured into a stainless steel mold to form a membrane, and then transferred to 80°C for vacuum drying to constant weight; the obtained membrane is immersed in 2 mol / L sulfuric acid for 24 hours to completely protonate it, and then the membrane is stored in deionized water before use.

[0045] The stress-strain curve of the CS-S-3 proton exchange membrane prepared in this example is as follows: Figure 2 The vanadium ion permeability and ion selectivity data are shown in Table 1.

[0046] Example 4

[0047] A method for preparing a two-component proton exchange membrane having a network structure comprises the following steps:

[0048] Step A, preparation of an amphoteric polymer with a multi-crosslinked structure: sulfonated polyetheretherketone (SPEEK, 2 g, DS = 80%) was added to a three-necked beaker, and dimethyl sulfoxide (DMSO, 20 g) was added and then stirred and dissolved; under a nitrogen environment, N, N'-carbonyldiimidazole (0.2 g) was added to the solution and reacted at 60°C for 3 hours; then 2,4,6-triamino-1,3,5-triazine (0.25 g) was added and the reaction continued at 60°C for 3 hours; after the reaction was completed, the obtained mixed solution was dialyzed with deionized water overnight, and then washed with deionized water 3 times to wash away the unreacted monomers therein, the solid product was collected, and finally dried to obtain an amphoteric polymer with a multi-crosslinked structure (CS-S-4);

[0049] Step B, preparation of amphoteric proton exchange membrane: the amphoteric polymer (1 g) obtained in step A is dried and dissolved in dimethyl sulfoxide (DMSO) (8 g), and a casting solution is obtained after mechanical stirring, ultrasound, and vacuum degassing, which is poured into a stainless steel mold to form a membrane, and then transferred to 80°C for vacuum drying to constant weight; the obtained membrane is immersed in 2 mol / L sulfuric acid for 24 hours to completely protonate it, and then the membrane is stored in deionized water before use.

[0050] The stress-strain curve of the CS-S-4 proton exchange membrane prepared in this example is as follows: Figure 2 As shown in Figure 1, the tensile strength of CS-S-4 membrane is increased by 1 times compared with the original SPEEK. The vanadium ion permeability and ion selectivity data are shown in Table 1.

[0051] Example 5

[0052] A method for preparing a two-component proton exchange membrane having a network structure comprises the following steps:

[0053] Step A, preparation of an amphoteric polymer with a multi-crosslinked structure: sulfonated polyetheretherketone (SPEEK, 2 g, DS = 80%) was added to a three-necked beaker, and dimethyl sulfoxide (DMSO, 20 g) was added and then stirred to dissolve; under a nitrogen environment, N, N'-carbonyldiimidazole (0.2 g) was added to the solution and reacted at 60°C for 3 hours; then tris (2-aminoethyl) amine (0.1 g) was added and the reaction continued at 60°C for 3 hours; after the reaction was completed, the obtained mixed solution was dialyzed with deionized water overnight, and then washed with deionized water 3 times to wash away the unreacted monomers therein, the solid product was collected, and finally dried to obtain an amphoteric polymer with a multi-crosslinked structure (CS-S-5);

[0054] Step B, preparation of amphoteric proton exchange membrane: the amphoteric polymer (1 g) obtained in step A is dried and dissolved in dimethyl sulfoxide (DMSO) (8 g), and a casting solution is obtained after mechanical stirring, ultrasound, and vacuum degassing, which is poured into a stainless steel mold to form a membrane, and then transferred to 80°C for vacuum drying to constant weight; the obtained membrane is immersed in 2 mol / L sulfuric acid for 24 hours to completely protonate it, and then the membrane is stored in deionized water before use.

[0055] The vanadium ion permeability and ion selectivity data of the CS-S-5 proton exchange membrane prepared in this example are shown in Table 1.

[0056] Example 6

[0057] A method for preparing a two-component proton exchange membrane having a network structure comprises the following steps:

[0058] Step A, preparation of an amphoteric polymer with a multi-crosslinked structure: sulfonated polyetheretherketone (SPEEK, 2 g, DS = 80%) was added to a three-necked beaker, and dimethyl sulfoxide (DMSO, 20 g) was added and then stirred to dissolve; under a nitrogen environment, N, N'-carbonyldiimidazole (0.2 g) was added to the solution and reacted at 60°C for 3 hours; then tris (2-aminoethyl) amine (0.15 g) was added and the reaction continued at 60°C for 3 hours; after the reaction was completed, the obtained mixed solution was dialyzed with deionized water overnight, and then washed with deionized water 3 times to wash away the unreacted monomers therein, the solid product was collected, and finally dried to obtain an amphoteric polymer (CS-S-6) with a multi-crosslinked structure;

[0059] Step B, preparation of amphoteric proton exchange membrane: the amphoteric polymer (1 g) obtained in step A is dried and dissolved in dimethyl sulfoxide (DMSO) (8 g), and a casting solution is obtained after mechanical stirring, ultrasound, and vacuum degassing, which is poured into a stainless steel mold to form a membrane, and then transferred to 80°C for vacuum drying to constant weight; the obtained membrane is immersed in 2 mol / L sulfuric acid for 24 hours to completely protonate it, and then the membrane is stored in deionized water before use.

[0060] The vanadium ion permeability and ion selectivity data of the CS-S-6 proton exchange membrane prepared in this example are shown in Table 1.

[0061] Example 7

[0062] A method for preparing a two-component proton exchange membrane having a network structure comprises the following steps:

[0063] Step A, preparation of an amphoteric polymer with a multi-crosslinked structure: sulfonated polyetheretherketone (SPEEK, 2 g, DS = 80%) was added to a three-necked beaker, and dimethyl sulfoxide (DMSO, 20 g) was added and then stirred to dissolve; under a nitrogen environment, N, N'-carbonyldiimidazole (0.2 g) was added to the solution and reacted at 60°C for 3 hours; then tris (2-aminoethyl) amine (0.2 g) was added and the reaction continued at 60°C for 3 hours; after the reaction was completed, the obtained mixed solution was dialyzed with deionized water overnight, and then washed with deionized water 3 times to wash away the unreacted monomers therein, the solid product was collected, and finally dried to obtain an amphoteric polymer with a multi-crosslinked structure (CS-S-7);

[0064] Step B, preparation of amphoteric proton exchange membrane: the amphoteric polymer (1 g) obtained in step A is dried and dissolved in dimethyl sulfoxide (DMSO) (8 g), and a casting solution is obtained after mechanical stirring, ultrasound, and vacuum degassing, which is poured into a stainless steel mold to form a membrane, and then transferred to 80°C for vacuum drying to constant weight; the obtained membrane is immersed in 2 mol / L sulfuric acid for 24 hours to completely protonate it, and then the membrane is stored in deionized water before use.

[0065] The vanadium ion permeability and ion selectivity data of the CS-S-7 proton exchange membrane prepared in this example are shown in Table 1.

[0066] Example 8

[0067] A method for preparing a two-component proton exchange membrane having a network structure comprises the following steps:

[0068] Step A, preparation of an amphoteric polymer with a multi-crosslinked structure: sulfonated polyetheretherketone (SPEEK, 2 g, DS = 80%) was added to a three-necked beaker, and dimethyl sulfoxide (DMSO, 20 g) was added and then stirred to dissolve; under a nitrogen environment, N, N'-carbonyldiimidazole (0.2 g) was added to the solution and reacted at 60°C for 3 hours; then tris (2-aminoethyl) amine (0.25 g) was added and the reaction continued at 60°C for 3 hours; after the reaction was completed, the obtained mixed solution was dialyzed with deionized water overnight, and then washed with deionized water 3 times to wash away the unreacted monomers therein, the solid product was collected, and finally dried to obtain an amphoteric polymer with a multi-crosslinked structure (CS-S-8);

[0069] Step B, preparation of amphoteric proton exchange membrane: the amphoteric polymer (1 g) obtained in step A is dried and dissolved in dimethyl sulfoxide (DMSO) (8 g), and a casting solution is obtained after mechanical stirring, ultrasound, and vacuum degassing, which is poured into a stainless steel mold to form a membrane, and then transferred to 80°C for vacuum drying to constant weight; the obtained membrane is immersed in 2 mol / L sulfuric acid for 24 hours to completely protonate it, and then the membrane is stored in deionized water before use.

[0070] The vanadium ion permeability and ion selectivity data of the CS-S-8 proton exchange membrane prepared in this example are shown in Table 1.

[0071] The Nafion membranes used in Comparative Examples 1 and 2 were purchased from DuPont and their models were Nafion 117 and Nafion 212, respectively.

[0072] Table 1 Vanadium ion permeability and ion selectivity data of proton exchange membranes at different crosslinking agent dosages

[0073]

[0074]

[0075] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention is described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a two-component proton exchange membrane having a network structure, characterized in that: The following steps are involved: Step A, preparation of an amphoteric polymer with a multi-crosslinked structure: sulfonated aromatic polymer: organic solvent: initiator A: crosslinker B are mixed in a mass ratio of 20 parts: 200 parts: 2 parts: 1-4 parts, the sulfonated aromatic polymer is added to a three-necked beaker, and the organic solvent is added and then stirred and dissolved; in a nitrogen environment, initiator A is added to the solution and reacted at 60° C. for 3 hours; then crosslinker B is added and the reaction is continued at 60° C. for 3 hours; after the reaction is completed, the obtained mixed solution is dialyzed with deionized water overnight, and then washed with deionized water 3 times to wash away the unreacted The monomer is prepared, and the solid product is collected and finally dried at 80°C for 24 hours to obtain an amphoteric polymer with a multi-crosslinked structure; step B, preparation of an amphoteric proton exchange membrane: the amphoteric polymer: organic solvent is mixed in a mass ratio of 1 part: 8 parts, the dried amphoteric polymer obtained in step A is dissolved in an organic solution, mechanically stirred, ultrasonicated, and vacuum degassed to obtain a casting solution, which is poured into a stainless steel mold to form a membrane, and then transferred to 80°C for vacuum drying to constant weight; after vacuum drying, the obtained membrane is immersed in 2 mol / L sulfuric acid for 24 hours to completely protonate it, and then the membrane is stored in deionized water before use.

2. The method for preparing the two-component proton exchange membrane having a network structure according to claim 1, characterized in that: In the step A, the sulfonation degree of the sulfonated aromatic polymer is above 75%.

3. The method for preparing the two-component proton exchange membrane having a network structure according to claim 1, characterized in that: The sulfonated aromatic polymer is one or more of sulfonated polyetheretherketone, sulfonated polyaryletherketone, sulfonated polyarylethersulfone and sulfonated polysulfone.

4. The method for preparing the two-component proton exchange membrane having a network structure according to claim 1, characterized in that: In the step A, the initiator A is a substance that can activate the sulfonic acid group, and the intermediate product thereof can continue to react further with the cross-linking agent B containing an amino functional group.

5. The method for preparing the two-component proton exchange membrane having a network structure according to claim 1, characterized in that: The initiator A is one or more of N,N'-dicyclohexylcarbodiimide, 1-ethyl-(3-dimethylaminopropyl)carbodiimide, and N,N'-carbonyldiimidazole.

6. The method for preparing the two-component proton exchange membrane having a network structure according to claim 1, characterized in that: In the step A, the crosslinking agent B is a substance containing multiple amino groups.

7. The method for preparing the two-component proton exchange membrane having a network structure according to claim 1, characterized in that: The crosslinking agent B is one or more of 2,4,6-triamino-1,3,5-triazine, tris(2-aminoethyl)amine, 2,4,6-tris(4-aminophenoxy)-1,3,5-triazine, 2,4,6-tris(4-aminophenyl)-1,3,5-triazine, tris(4-aminophenyl)amine, and triaminoguanidine hydrochloride.

8. The method for preparing the two-component proton exchange membrane having a network structure according to claim 1, characterized in that: The organic solvent is an organic small molecule solvent that can dissolve the sulfonated aromatic polymer, the initiator A and the crosslinking agent B and will not react with them.

9. The method for preparing the two-component proton exchange membrane having a network structure according to claim 1, characterized in that: The organic solvent is one or more of dimethyl sulfoxide, N,N'-dimethylformamide and N,N'-dimethylacetamide.

Citation Information

Patent Citations

  • A proton exchange film for direct carbinol fuel battery and its making method

    CN101188301A

  • Sulfonated polyether ether ketone capable of being used as crosslinking proton exchange membrane material and purpose thereof

    CN106117473A

  • Novel high-stability cross-linked sulfonated polyether-ether-ketone as well as preparation method and application thereof

    CN110483711A

  • Cross-linkable poly(arylene ether ketone) with sulfonated backbone comprising pendant ester structure, polymer electrolyte membrane for fuel cell prepared therewith and preparation method thereof

    KR1020120065179A

Cited By

  • Preparation method of phosphoric acid doped melamine modified sulfonated polyetheretherketone composite membrane

    CN120737403A